ANALISIS TRANSMISI KEBIJAKAN MONETER SYARIAH DALAM RANGKA ITFDENGAN METODE VAR - Aliman Syahuri Zein (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
Based on the results of the study concluded that the stationary test result data by using the ADF was found that the variable INF and LnBMBB stationary without differentiation. Meanwhile, TBHP stationary with differentiation.While based on the optimum lag test criteria SC found that the optimal lag length is at lag 2. Granger causality test found a one-way relationship of LnBMBB to INF, TBHP to INF, and TBHP to LnBMBB. These findings suggest that changes in the past BMBB have an influence on the level of inflation at the present time, TBHP change the past affects the present rate of inflation. TBHP change the past affects the present rate of inflation. For cointegration test, it was found that the variable contains cointegration studies, so that the method used for the study is the method VECM.Based on the VECM estimation, the long-term effect on INF BMBB significant, whereas no significant effect on INF to TBHP. Meanwhile, for the short term, the only significant variable TBHP to BMBB.IRF test results concluded that the turmoil/response of inflation to BMBB positive impact and volatile and stable from period 13. While INF against d(TBHP) negative and volatile, stable from period 15.The LnBMBB response to d(TBHP), or otherwise negatively. Referring to the VD, concluded that the inflation rate is influenced most by himself in the first period by 100 %, then by LnBMBB at 1:16 % in the period to 6, and the last is influenced by d ( TBHP ) is very small, in the period to 2 only for 0:47 %.